Study on engine performance and exhaust pollutant using isobutanol - Calophyllum inophyllum biodiesel - diesel ternary blends in a diesel engine / Mohd Azham Mohd Alwi - Mohd Azham, Mohd Alwi (2021)
Renewable energy sources such as biodiesel and bio-alcohol are desirable and are alternative to meet energy demand and control emission, from renewable sources such as ethanol, methanol, butanol, and pentanol. Biodiesel has a notable interest in offering many advantages with few disadvantages and needs to be extended for comprehensive use. Applying greater alcohols such as butanol with biodiesel in fuel blends is a beneficial technic to enhance the fuel characteristics and use biodiesel and alcohol efficiently. Isobutanol is an organic compound that has very low volatility, higher-chain alcohols have energy densities close to gasoline. It is not as volatile or corrosive as ethanol and does not readily absorb water. Furthermore, branched chain of alcohols such as isobutanol have higher-octane numbers resulting in less knocking in engines. The molecule has nearly 20 percent higher energy density compared to ethanol. The chemical structure and its production from renewable sources can enhance energy security and environmental challenges. To assess the suitability of isobutanol with biodiesel diesel blends and reveal the effects of it, 5%, 10% and 15% of isobutanol were blended with 5%, 10% and 15% of Calophyllum inophyllum biodiesel to enhance the fuel features and make them more viable with better engine efficiency. The experiment was carried out under distinct load circumstances on a single-cylinder compression ignition diesel engine, four-stroke, water-cooled, direct injection diesel engine, 1.97 bar to 7.88 bar brake mean effective pressure (BMEP). The fuel characteristics, engine efficiency, and exhaust pollutants were assessed and compared to biodiesel blends and diesel from petroleum. From the experiment, it is been discovered that the diesel engine operating with higher alcohol-biodiesel blended fuels has shown higher brake specific energy consumption and exhaust gas temperature, but lower brake thermal efficiency. Then, the HC, CO, and CO2 are decreased for all higher alcohol- biodiesel blended fuels. However, NOx, showed an increasing trend due to the increase of injection quantity and lower cetane number. It can be proved that isobutanol may be utilized as a preferential substitution with biodiesel and petroleum diesel.